Tetrodotoxin (TTX) Time–Resolved Absorption and Resonance FT–IR and Raman Biospectroscopy and Density Functional Theory (DFT) Investigation of Vibronic–Mode Coupling Structure in Vibrational Spectra Analysis - Heidari, Alireza; Esposito, Jennifer; Caissutti, Angela (Journal of New Developments in Chemistry, 2019)
Tetrodotoxin (TTX) is a potent neurotoxin. Its name derives from Tetraodontiformes, an order that includes pufferfish, porcupinefish, ocean sunfish, and triggerfish; several of these species carry the toxin. Although tetrodotoxin was discovered in these fish and found in several other aquatic animals (e.g., in blue–ringed octopuses, rough–skinned newts, and moon snails), it is actually produced by certain infecting or symbiotic bacteria like Pseudoalteromonas, Pseudomonas, and Vibrio as well as other species found in animals. Parameters such as FT–IR and Raman vibrational wavelengths and intensities for single crystal Tetrodotoxin (TTX)are calculated using density functional theory and were compared with empirical results. The investigation about vibrational spectrum of cycle dimers in crystal with carboxyl groups from each molecule of acid was shown that it leads to create Hydrogen bounds for adjacent molecules. The current study aimed to investigate the possibility of simulating the empirical values. Analysis of vibrational spectrum of Tetrodotoxin (TTX) is performed based on theoretical simulation and FT–IR empirical spectrum and Raman empirical spectrum using density functional theory in levels of F/6–31G*, HF/6–31++G**, MP2/6–31G, MP2/6–31++G**, BLYP/6–31G, BLYP/6–31++G**, B3LYP/6–31G and B3LYP6–31–HEG**. Vibration modes of methylene, carboxyl acid and phenyl cycle are separately investigated. The obtained values confirm high accuracy and validity of results obtained from calculations. Molecular structure of Tetrodotoxin (TTX) 1–42.
Keywords: Tetrodotoxin; Density Functional Theory; Vibrational Spectra; Neurotoxin; Hydrogen